DAILY JOURNAL VOCABULARY USED IN LEARNING ENGLISH AT SMPN 3 SAMBALIUNG - Rahmaya, Putri Ayu; Cahyani, Nur; Fitrah, Zul; Sari, Ita Novita; Dwi Ariyani, Helda Anastasya (ITB AAS Indonesia Surakarta, 2024)
Vocabulary is aspect important in learn Language foreign . If you do not understand vocabulary with well , your ability to speak , read , and write Language English will limited . Techniques for implementing daily journaling can be done applied in learning Language English For increase memorize vocabulary . Systematic and repetitive activities _ can increase Power remember student . Researcher use method qualitative . Data collection was carried out with observation , questionnaires and interviews. Researcher find that student class VIII at SMPN 3 Sambaliung experience difficulty in learn vocabulary Language English.Engineering implementing a daily diary can become techniques that can applied in learning Language English Because combine activity reading and writing are done in a way routine For increase ability student in remember vocabulary . Implementation results vocabulary journalism everyday in junior high school students show results positive based on the average of post-test results and responses interview student . Student consider technique This effective . This matter supported with increase student vocabulary _ during the learning period after use Daily Vocabulary technique. Keywords: Daily Journal, Vocabulary, Learning